2017
DOI: 10.1007/s13201-017-0532-6
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate statistical techniques for the evaluation of surface water quality of the Himalayan foothills streams, Pakistan

Abstract: Himalayan foothills streams, Pakistan play an important role in living water supply and irrigation of farmlands; thus, the water quality is closely related to public health. Multivariate techniques were applied to check spatial and seasonal trends, and metals contamination sources of the Himalayan foothills streams, Pakistan. Grab surface water samples were collected from different sites (5-15 cm water depth) in pre-washed polyethylene containers. Fast Sequential Atomic Absorption Spectrophotometer (Varian FSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The quality of a river at any point reflects major influences, including the lithology of the basin, atmospheric inputs, climatic conditions and anthropogenic inputs (Bricker and Jones 1995;Reza and Singh 2010;Herojeet et al 2015b;Jung et al 2016). On the other hand, rivers play a major role in assimilation or transporting multitude of pollutants present in municipal and industrial wastewater and runoff from agricultural land (Qadir et al 2008;Wang et al 2013;Malik and Hashmi 2017). Municipal and industrial wastewater discharge constitutes a constant polluting source, whereas surface runoff is a seasonal phenomenon, largely influenced by climate within the basin (Singh et al 2004;Kumar et al 2015;Bhutiani et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The quality of a river at any point reflects major influences, including the lithology of the basin, atmospheric inputs, climatic conditions and anthropogenic inputs (Bricker and Jones 1995;Reza and Singh 2010;Herojeet et al 2015b;Jung et al 2016). On the other hand, rivers play a major role in assimilation or transporting multitude of pollutants present in municipal and industrial wastewater and runoff from agricultural land (Qadir et al 2008;Wang et al 2013;Malik and Hashmi 2017). Municipal and industrial wastewater discharge constitutes a constant polluting source, whereas surface runoff is a seasonal phenomenon, largely influenced by climate within the basin (Singh et al 2004;Kumar et al 2015;Bhutiani et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Qamar et al (2017) showed that vehicle washing contaminates water with compounds of petrogenic and pyrogenic origin, mainly polycyclic aromatic hydrocarbons (PAHs), that enter the main water tributaries and end up entering human food chain, causing carcinogenic and mutagenic diseases in consumers. Moreover, heavy metals such as barium, lead, chromium and nickel, that pose a risk to health, are found to be linked to fuel combustion and vehicle washing runoff (Bashir et al, 2017; Malik and Hashmi, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The management of the Islamabad is under the supervision of the Capital Development Authority (CDA), which has all the protocols and guidelines for the management and expansion of the city [63], while Rawalpindi is managed by the Rawalpindi Development Authority (RDA) [64]. In addition, the weak enforcement of the law in Rawalpindi has stimulated the encroachment of government land and the development of illegal housing societies, causing haphazard urbanization [65]. In 2017, the Capital Development Authority of Islamabad (CDA) demolished 50 commercial buildings, including marriage halls and shops on illegal land worth PKR 9 billion (USD 51,660,765), as well as 1670 ha of land costing PKR 300 billion (USD 1,722,025,500), which was retrieved from the land grabbers [66].…”
Section: Discussionmentioning
confidence: 99%